PENGARUH DISIPLIN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA DAPUR ARANG A ENG DI PULAU MANDA - Chandra Wijaya; Jontro Simanjuntak (SOSCIED, 2022)
Human resources have an important role so that management activities run smoothly so that employees who are educated and have competent skills are needed to achieve company goals. The research entitled The Influence of Discipline, Motivation and Compensation on Employee Performance at Dapur Arang A Eng because it requires employee participation in terms of work discipline, motivation and compensation. The research objectives are to determine: (1) The effect of discipline on the performance of Dapur Arang A Eng employees, (2) The effect of motivation on the performance of Dapur Arang A Eng employees, (3) The effect of compensation on the performance of Dapur Arang A Eng employees, (4) the influence of discipline , motivation and compensation on the performance of employees of Dapur Arang A Eng. The technique of this research is to identify the effect of partial (t test) and simultaneous (F test) between the variables of work discipline, motivation and compensation on employee performance at Dapur Arang A Eng. The research method used is descriptive research method with quantitative applications, data analysis using SPSS version 26 software program. Data collection techniques were carried out by distributing questionnaires to 118 respondents. The results show that the R Square value of the work discipline, motivation, and compensation variables affects employee performance while the t-test for work discipline consists of a value of 2,460 > 1,658 with a significant value of 0.015 < 0.05, motivation has 5.442 > 1.658 and a significant value of 0.000 < 0 .05 and compensation to give a value of 2.121 > 1.658 and a significant value of 0.036 < 0.05. Each variable has a significant effect on employee performance and the F test results consist of a value of 117 of 73.524 > 2.68 and a significant value of 0.000 < 0, 05 which shows that discipline, motivation and compensation simultaneously have a significant effect on employee performance.